A deterministic and stochastic approach to analyze carbon tetrachloride-induced liver injury in rats - Ngadikun, Ngadikun (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
A new spectrometrical method was developed to determine a marker for liver damage. The aims of this study wasto investigate the pattern of cellular interaction in EDTA-blood spectrometrically in rats that induced by carbontetrachloride (CCl4). Eight of white male rats (Rattus norvegicus L), aged of 2 months with body weight of 160-210g were divided into two groups with 4 rats in each group. The first group as control were not fed and the secondgroup as treatment were fed with 0.1 mL/kgBW CCl4 for 21 weeks. At the end of the experiment, rats were fastedovernight, 3.0 mL of blood was drawn from the vena orbitalis for spectrometrical and biochemical estimation. Ratswere then sacrificed and the liver tissue was used for histological assessment. All data were analyzed with t-test.Histopathological studies of treated group showed the damage of the liver cells compared with control group. Theresults showed no significant difference in ALT (p = 0.12) and AST (p = 0.19) but significant difference in AST/ALT ratio (p = 0.01) between 2 groups was observed. The deterministic and stochastic approaches showed nosignificant differences in k7 (p = 0.11) but significant difference in k6 (p = 0.00) and k8 (p = 0.00). It wasconcluded that the combination of deterministic and stochastic approaches can be used to determine a marker forliver damage.Key words : CCl4-induced liver injury â dendrogram â deterministic - stochastic approach - non-functional plasmaenzymes - Rattus norvegicus.